Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems 2018
DOI: 10.1145/3173574.3174193
|View full text |Cite
|
Sign up to set email alerts
|

Morphees+

Abstract: Users interact with many reconfigurable objects in daily life. These objects embed reconfigurations and shapechanging features that users are familiar with. For this reason, everyday reconfigurable objects have informed the design and taxonomy of shape changing UI. However, they have never been explored systematically. In this paper, we present a data set of 82 everyday reconfigurable objects that we collected in a workshop. We discuss how they can inspire the design of reconfigurable interfaces. We particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 53 publications
0
18
0
3
Order By: Relevance
“…We use the term reconfigurable interface defined by Kim et al. [20] to refer to interfaces that can have different shapes and can be distorted by the user's input or by the system. This type of interface is also called malleable, deformable or shape changing.…”
Section: Reconfigurable Devicesmentioning
confidence: 99%
“…We use the term reconfigurable interface defined by Kim et al. [20] to refer to interfaces that can have different shapes and can be distorted by the user's input or by the system. This type of interface is also called malleable, deformable or shape changing.…”
Section: Reconfigurable Devicesmentioning
confidence: 99%
“…We used the existing interaction of rotating and sliding the devices for value input and added other modalities to input uncertainty. We used the features of the Morphees+ taxonomy [11] to design the additional modalities (see Figure 1). The designs quantify uncertainty in two ways: the dials and Expandable Slider (Figure 1a…”
Section: Design Exploration For Uncertain Input Tuismentioning
confidence: 99%
“…In this work-in-progress, we explore the design of physical dials and sliders that can capture users' value and uncertainty on one device. We first use Morphees+ [11] features to design 5 controls that can input both value and uncertainty, which are based on ordinary dials and sliders. We then present low-fidelity prototypes and conduct a focus group study to gather feedback on them.…”
Section: Introductionmentioning
confidence: 99%
“…Shape-changing tangible interfaces can also be used to combine different elements such as sliders or knobs in a single component [21]. Studies on shape-changing interfaces can be found in [7,22]. These interfaces provide an interesting approach in the area of dynamic and adaptable interfaces, however, they also entail relatively complex hardware and high cost.…”
Section: Dedicated Tangible Interfacesmentioning
confidence: 99%